Komunikasi Politik dan Branding Pemimpin Politik Melalui Media Sosial: A Conceptual Paper - Festy Rahma Hidayati (JURNAL LENSA MUTIARA KOMUNIKASI, 2021)
The presence of digital media, such as social media allows us to connect without any limitations of space and time. Consumption of social media brings changes in various aspects of life, including the habits of communicating and interacting in today's network society. In the political field, social media creates opportunities for political leaders to carry out political communication. As a strategic political communication channel, social media plays a role in receiving and responding to public aspirations. In fact, the use of social media for campaigns by political leaders shows a trend of increasing popularity and electability due to the influence of branding on social media. The use of social media by political leaders in building specific branding is at the core of this article. Political leaders optimize their personal social media accounts for political communication. The positive perception of the public allows for an increase in popularity and electability which brings to the national political stage. This article is a conceptual paper that analyzes the concept of branding in politics in the era of digital political communication by utilizing social media. The author uses relevant literature reviews from previous studies. This article reveals that several political leaders that have been studied have optimized social media to carry out political communication to their citizens. They display digital content to gain public support and trust, and display branding as a populist, professional, humanist, and responsible political leader.